Developing a Cancer-Focused Library Survey — Assessing the Current Environment and Planning for the Future. Issue 1 (2nd January 2019) - Fulton, Stephanie; Gibson, Donna S.; Orick, Jan; Clark, Ann Marie
Abstract: The primary goal of this project is to understand how each National Cancer Institute-designated cancer center library, and all libraries that support cancer research, function within their institutions. Through an in-depth survey focused on three major areas (staff, content and tools procurement, and user services), the research team hopes to determine how a cancer-centric library can be successful in supporting quality patient care, research excellence, and education. Additionally, the survey will examine the necessary minimum staffing levels for librarians and information professionals based on organizational size and degree of research focus. The survey will seek out the new skills librarians will need to deliver optimal services. The survey will also explore how content libraries purchase reflects and maps to constituents' current medical and research activities. Libraries within a research intense environment have a responsibility to align with researchers and health care professionals to provide resources and services that support their workflows. Cancer libraries need to be attuned to their institutions' missions, whether that includes excellent patient care, research endeavors, or cutting-edge educational programs. The information gathered from the survey will provide data for this research team to define the vision and standards of excellence for a cancer specialized research library.